UML IMPLEMENTATION IN WEB-BASED MONTHLY GARBAGE FEE SYSTEM OF GINTUNG KEBON HAMLET - Fadilah, Aluthfi (Universitas Lampung, 2025)
Rukun Tetangga/Rukun Warga (RT/RW) is an institution formed through community deliberations at the local community level with the aim of preserving and nurturing values based on the spirit of mutual cooperation and familial bonds. One common issue in community environments is waste management. Therefore, waste management is not solely the exclusive responsibility of the government but requires extensive involvement from the community as a whole. The current technological advancements provide convenience in daily activities. In this rapid technological progress, the mobile device sector, also known as smartphones, is also impacted. By implementing the SDLC (Software Development Life Cycle) method with a waterfall model, the results and analysis indicate the need for modeling to facilitate the design of the required system. The goal is to provide a modeling language that is independent of various programming languages and engineering processes. The creation of a web-based waste collection system aims to facilitate the residents of RT/RW in paying waste collection fees. It is hoped that this website can help streamline and make the payment process more effective.